Role of daytime variation in pharmaceutical effects of sufentanil, dezocine, and tramadol: A matched observational study - Gan, Wanxia; Yang, Xinqing; Chen, Jie; Lyu, Hongyao; Yan, Ai; Chen, Guizhen; Li, Shiqi; Zhang, Yamei; Dan, Ling; Huang, He; Duan, Guangyou (Frontiers in Pharmacology, 2022)
The role of daytime variation in the comprehensive pharmaceutical effects of commonly used opioid analgesics in clinical setting remains unclear. This study aimed to explore the differences in daytime variation among elective surgery patients who were scheduled to receive preemptive analgesia with equivalent doses of sufentanil, dezocine, and tramadol in the morning and afternoon. The analgesic effect was assessed by changes in the pressure pain threshold before and after intravenous administration of sufentanil, dezocine, and tramadol. Respiratory effects were evaluated using pulse oximetry, electrical impedance tomography, and arterial blood gas analysis. Other side effects, including nausea, sedation, and dizziness, were also recorded, and blood concentration was measured. The results showed that the analgesic effects of sufentanil, dezocine, and tramadol were significantly better in the morning than in afternoon. In the afternoon, sufentanil had a stronger sedative effect, whereas dezocine had a stronger inhibitory respiratory effect. The incidence of nausea was higher in the morning with tramadol. Additionally, significant differences in different side effects were observed among three opioids. Our results suggest that the clinical use of these three opioids necessitates the formulation of individualized treatment plans, accounting for different administration times, to achieve maximum analgesic effect with minimal side effects.